New approach for estimating total mining costs in surface coal mines - Shafiee, S.; Topal, Erkan (Maney Publishing, 2012)
Accurate cost estimation is a critical component of mining project evaluation to determine whether the proposed project is clearly feasible, doubtfully feasible or clearly uneconomic. At the beginning of the process, it is very difficult for project evaluators to find reliable relevant data that can be used for all phases of the cost estimation. This paper provides an overview of published work on mining cost estimation methods, data sources and available software. It also introduces the concept of indices for different components of mining projects, discusses their historical movements, and then it compares mining cost indices in the USA, Canada and Australia. It also introduces a new econometric model for estimating the operating cost and capital cost of a coalmining project. The total operating cost and capital cost of mining are calculated by using the proposed econometric model and verified by comparing the outputs with CostMine data and Sherpa software outputs for a surface coal mine. The model shows that the capital cost and production rate have a negative effect on the operating cost, while the deposit average thickness and stripping ratio have a positive effect.